Regulation of flowering time by the miR156-mediated age pathway - Wang, Jia-Wei (Journal of experimental botany, 2014)
Precise flowering time is critical to reproductive success. In response to diverse exogenous and endogenous cues including age, hormones, photoperiod, and temperature, the floral transition is controlled by a complex regulatory network, which involves extensive crosstalks, feedback, or feedforward loops between the components within flowering time pathways. The newly identified age pathway, which is controlled by microRNA156 (miR156) and its target SQUAMOSA PROMOTER BINDING-LIKE (SPL) transcription factors, ensures plants flower under non-inductive conditions. In this review, I summarize the recent advance in understanding of the age pathway, focusing on the regulatory basis of the developmental decline in miR156 level by age and the molecular mechanism by which the age pathway is integrated into other flowering time pathways.